2019
DOI: 10.1038/s41467-019-09426-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of flying cars in sustainable mobility

Abstract: Interest and investment in electric vertical takeoff and landing aircraft (VTOLs), commonly known as flying cars, have grown significantly. However, their sustainability implications are unclear. We report a physics-based analysis of primary energy and greenhouse gas (GHG) emissions of VTOLs vs. ground-based cars. Tilt-rotor/duct/wing VTOLs are efficient when cruising but consume substantial energy for takeoff and climb; hence, their burdens depend critically on trip distance. For our base case, traveling 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(79 citation statements)
references
References 18 publications
(15 reference statements)
4
62
0
2
Order By: Relevance
“…We consider the limitation of our LCA to global warming reasonable, as it is one of the most pressing sustainability issues to date [17]. Also, this approach is in line with the referenced study by Kasliwal et al [9].…”
Section: Life Cycle Assessmentmentioning
confidence: 86%
See 1 more Smart Citation
“…We consider the limitation of our LCA to global warming reasonable, as it is one of the most pressing sustainability issues to date [17]. Also, this approach is in line with the referenced study by Kasliwal et al [9].…”
Section: Life Cycle Assessmentmentioning
confidence: 86%
“…A study recently published in 'nature Communications' by Kasliwal et al demonstrates that eVTOL may, in a constrained scenario, be able to environmentally compete with internal combustion engine vehicles, and possibly with battery electric vehicles [9]. The authors demonstrate the criticality of trip distance for the overall carbon efficiency and show that eVTOL can, in certain cases, beat ground-based cars in terms of emissions per passenger transported.…”
Section: Introductionmentioning
confidence: 99%
“…Without effective resolutions such as new or reconfigured runways, congestion at major airports is expected to cause more and more delays in travel time and unnecessary costs for both airlines and passengers. In this context, in the last decade, technical advancement with the potential civil VTOL transport has gained significant interest both in research and investment due to the multiple socio-economic factors, such as massive fuel costs, noise reduction, and user benefits in the air transportation industry (Kasliwal et al, 2019).…”
Section: Background Of the Studymentioning
confidence: 99%
“…• Goal 4: Competitive operation and maintenance costs. VTOL is efficient when it cruises but consumes substantial energy for takeoff and climb (Kasliwal et al, 2019). Also, because lift engines serve as deadweight while cruising, more weight and distance it needs to transport, which means more fuel needs to be consumed.…”
Section: ) Enabler: Competitive Vtol Technologymentioning
confidence: 99%
“…The concept promises to remove some traffic from the roads and to move it to the uncongested skies, thus reducing some of the negative effects of the car. While the positives of the concept are yet subject to research (some results can be found in [7], suggesting that under some circumstances VTOLs can be more energy efficient than ground vehicles), it is interesting to evaluate what may be the actual market penetration of such a service around the world. In the near future, as the technology is yet to mature, it is expected that the service will be costly and only accessible to the few, as was the case for both automobile and long-distance aircraft travel.…”
Section: Introductionmentioning
confidence: 99%